The political ecological economics of coal mining and water resources: a participatory economic valuation approach in Carolina, Mpumalanga - Nzimande, Nqobile (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2020)
Globally, resource economic valuation has traditionally focused on monetary and market-based methods. However, there has been a recent move towards more transdiciplinary methods that encourage civil participation in resource economic valuation studies with the aim of generating more site-specific and appropriate values which can potentially improve natural resource management decisions. With a focus on Carolina, this thesis investigated whether citizen based participatory approaches can result in more appropriate resource economic values that reflect the social environmental values in Carolina. A qualitative research approach was adopted for this research which incorporated questionnaires and semi-structured interviews. The research also adopted an inductive thematic analysis. The findings of the research showed that local scale stakeholders have different perceived values of natural resources. The research further showed that national scale resource governance institutions deal with issues of natural resource economic conflicts related to environmental policy and decision making. The study will contribute to deepening an understanding of the contribution that a natural resource economics assessment, or analysis can have on equitable, sustainable and efficient water resource management in the face of water-use contestation
Keywords: Natural resources -- Management; Natural resources -- Management -- South Africa -- Carolina; Natural resources -- Valuation; Natural resources -- Valuation -- South Africa -- Carolina; Coal mines and mining -- Environmental aspects -- South Africa -- Carolina; Water-supply -- South Africa -- Carolina; Water-supply -- Government policy -- South Africa -- Carolina; Water conservation -- South Africa